Latin America looking for its autonomy: the (im) possibility of concerting between the foreign policies of Brazil and Mexico | A América Latina em busca de sua autonomia: a (im)possibilidade de concertação entre as políticas externas do Brasil e do México - Miranda Delgado, Rafael Gustavo; Hoyos Valera, Alberto (Mural Internacional, 2022)
Latin America as a region, has been losing relevance and agency capacity in the Global Order. Regionalism continues to be a pending task, which is why it is not presented as a unitary actor in the Global Order. Therefore, this research aims to analyse the impact that the divergence of the foreign policies of Brazil and Mexico has had on the search for Latin American autonomy. The hypothesis that guides this research is that the impossibility of concerting the foreign policies of Brazil and Mexico has made it difficult for Latin America to present itself as a unitary regional actor in the Global Order, which prevents its autonomy. Keywords: Autonomy; Regionalism; Foreign policy. RESUMO A América Latina, como região, vem perdendo relevância e capacidade de agenciamento na Ordem Global. O regionalismo continua sendo uma tarefa pendente, por isso não se apresenta como um ator unitário na Ordem Global. Portanto, esta pesquisa tem como objetivo analisar o impacto que a divergência das políticas externas do Brasil e do México teve na busca pela autonomia latino-americana. A hipótese que norteia esta pesquisa é a de que a impossibilidade de concertação das políticas externas do Brasil e do México dificulta que a América Latina se apresente como um ator regional unitário na Ordem Global, impedindo sua autonomia. Palavras-chave: Autonomia; Regionalismo; Política estrangeira. Recebido em: 06 out. 2022 | Aceito em: 05 dez. 2022.